Guaranteed Employment, Work Incentives, and Welfare Reform: Insight from the Work Equity Project - Wilson, Stephanie H.; Steinberg, Danny D.; Kulik, Jane C (American Economic Review, 1980)
Interest in national welfare reform has generated several recent income-maintenance and employment and training demonstration projects targeted at welfare recipients and low-income persons. Incomemaintenance programs typically operate by providing cash grants to poor families in amounts decreasing with earned income. Employment and training programs focus on increasing employability through skill development and job placement. While income maintenance strategies address problems of poverty and income inequality, they do not consider the capability of the disadvantaged to achieve economic independence; also, marginal tax rates on benefits have been found to decrease labor supplied (see Michael Keeley et al.). Programs employing a social services and training approach address the issues of employment and labor supply more directly. Analysis of one such program, however, suggests only slight increments to annual earnings have accrued in the postprogram period, and these only for a select group of participants (see Bradley Schiller). Several explanations for these outcomes can be posited, one being that barriers to employability of welfare and low-income persons have not been adequately assessed or remedied. Many of these persons are unmarried female heads of household with little prior work experience, job skills, or labor market familiarity. Real barriers to employability exist for these women, some of which can be corrected via a regimen of training and improvement of existing skills, and others which are more difficult to ascertain and correct. These barriers must be overcome before individuals can be expected to benefit from any program designed to reduce their dependence on welfare. Once these barriers are overcome incentives may be used to increase their commitment to the workforce and to foster economic self-sufficiency. The Minnesota Work Equity Project was funded as a two-year demonstration, employment, and training program serving clients from a variety of public assistance programs (AFDC, GA, Food Stamp) via a common service delivery system. This experiment addresses issues of barriers to employability and incentive to work by guaranteeing a job to all clients deemed employable according to statutory criteria. Employable clients are in effect required to work as one aspect of program services, though emphasis is on employability development through counseling or training. In this paper we identify barriers to employability faced by Work Equity Program clients using preliminary data from the first months of program operation. We analyze clients' five-year preprogram work histories, determinants of the decision to work, and returns to labor market investments. We also discuss clients' reservation wage expectations which provide information about labor market orientation. Finally, we discuss policy implications of these results. *Abt Associates Inc., Harvard University and Abt Associates Inc., and University of Chicago and Abt Associates Inc., respectively. This paper is based on a larger report prepared under contract with the U.S. Department of Labor. We would like to thank Ernst W. Stromsdorfer, principal investigator of the Work Equity Project evaluation, for advice and encouragement throughout our work on this project, and for many helpful remarks on earlier drafts of this paper. The opinions expressed here are our sole responsibility and should not be attributed to the U.S. Department of Labor or any agency or other individuals associated with the Work Equity Project.